The musculorelaxants consumption in inhalation and intravenous anaesthesia - Erhan, Ömer L.; Yaşar, M. Akif; Beştaş, Azize; Avci, Levent; Okuducu, Hasan (My University, 2004)
In general anaesthesia (inhalation and total intavenous) musculorelaxants are being used during laringoscopy-intubation. Halogeneous inhalation agents potantiate the effect of little/more nondepolarisant musculorelaxants, however this effect is unknown in total intravenous anaesthesia (TIVA). In our study we searched the expenditure of the vecuronium in both inhalation anaesthesia and TIVA. After tha regional ethical commitee approval, the ASA I and II cases randomly grouped. Eighty two cases were in inhalation anaesthesia groups (Group I; 40 patients, isoflurane+vecuronium, Gropup II; 42 patients, sevoflurane+vecuronium) and 50 patients were in TIVA group (Group III; propofol+vecuronium). Vecuronium was applied to all patients 0.08 mg kg -1 intravenous after induction and additional doses of 0.02 mg kg-1 intravenous were applied when needed. Kruskal-Wallis variance analysis is used for statistically analysis between groups. There was no statistically significant differences in anaesthesia duration between groups. Avarage vecuronium expenditure in group I was 0.01±0.07 mg min -1, in Group II 0.01±0.09 mg min-1, in Group III 0.01±0.07 mg min-1, the difference was not statistically meaningful (p=0.2038). Both sevoflurane and isoflurane increased vecuronium effect however the myorelaxant effect of propofol that is used commonly used in TIVA is still unknown. EMG studies showed that propofol decreased the electrical activity which was the result of the central affects of propofol. In our study, statistically significant myorelaxant expenditure differences did not obtained between TIVA and inhalation anaesthesia techniques.
Total i?ntravenöz ve i?nhalasyon anestezisinin kas gevşetici ajan tüketimine etkileri
Keywords: Isoflurane; Myorelaxant; Propofol; Sevoflurane